2016
DOI: 10.1136/bmj.i3426
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, outcomes, and costs of implementing non-invasive prenatal testing for Down’s syndrome into NHS maternity care: prospective cohort study in eight diverse maternity units

Abstract: Objective To investigate the benefits and costs of implementing non-invasive prenatal testing (NIPT) for Down’s syndrome into the NHS maternity care pathway.Design Prospective cohort study.Setting Eight maternity units across the United Kingdom between 1 November 2013 and 28 February 2015.Participants All pregnant women with a current Down’s syndrome risk on screening of at least 1/1000.Main outcome measures Outcomes were uptake of NIPT, number of cases of Down’s syndrome detected, invasive tests performed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
160
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(183 citation statements)
references
References 37 publications
(51 reference statements)
18
160
2
3
Order By: Relevance
“…Results from two questionnaire studies also showed that NIPT will probably be used more readily in women who just want to prepare themselves 24, 25. In a UK study, where women were offered NIPT as a second screening test through the National Health Service (NHS), 31% (13/42) of women with a confirmed diagnosis of Down syndrome after NIPT continued the pregnancy, compared to 7% (2/29) after direct invasive testing 26. It needs to be established if this remains true once NIPT is fully incorporated in prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Results from two questionnaire studies also showed that NIPT will probably be used more readily in women who just want to prepare themselves 24, 25. In a UK study, where women were offered NIPT as a second screening test through the National Health Service (NHS), 31% (13/42) of women with a confirmed diagnosis of Down syndrome after NIPT continued the pregnancy, compared to 7% (2/29) after direct invasive testing 26. It needs to be established if this remains true once NIPT is fully incorporated in prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…NIPS has previously been shown to be a superior test compared with combined screening methods involving serum markers and ultrasound scanning. 2 Wald et al confirm the superiority of NIPS over the combined test when implemented in routine hospitalbased service in the United Kingdom. Furthermore, in the discussion section, the authors extrapolate findings to discuss the advantages of the reflex pathway over the contingent pathway.…”
mentioning
confidence: 97%
“…2 Therefore, in England and Wales, National Health Service commissioners have opted for an evaluative rollout of NIPS as a second-stage test in a population of pregnancies already found to have a higher chance of being affected by a trisomy by conventional methods (a "combined test" first stage).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach ("contingent screening") has been the subject of various studies. [3][4][5][6] A weakness with this approach is the need to recall women for counseling and to obtain an extra blood sample for the DNA screening test. This recall is likely to make the women acutely anxious; some may choose to proceed directly to an amniocentesis or chorionic villus sampling with the associated risks to the pregnancy.…”
Section: Introductionmentioning
confidence: 99%